Which Electoral System Ensures Real Representation?. Issue 1 (June 2019) - Vundru, Raja Sekhar
Abstract: The article focuses on the electoral thoughts and ideas of Ambedkar, Gandhi and Patel. Dr Ambedkar's efforts for the implementation of representative electoral system have been discussed, along with the evolution of electoral methods that determines every election in India. The article highlights the shortcomings of electoral methods adopted in India as socially marginalized groups and classes have always been underrepresented or represented inappropriately. The article also discusses the functioning of different electoral methods such as two round system and proportional representation system. The present electoral system adopted in India needs to be reformed as per Ambedkar's electoral ideas to ensure representative, inclusive and equitable democracy.